Peran Orangtua Dalam Menanamkan Pembiasaan Sedekah Pada Anak Usia Dini di RA KPM Al-Ikhlas Kabupaten Sukabumi - Mulyana, Yeni (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to determine the obstacles in instilling the habit of giving alms, and also to determine the role of parents in instilling the habit of giving alms in Early Childhood at RA KPM Al-Ikhlas, Sukabumi Regency. This study was conducted based on initial findings that the Friday alms activity carried out by children had been going on for quite a long time at the school. This alms activity is given a schedule by the teacher or school on Friday, so that with the active role of parents, it is seen that every Friday the children are always on their own. The study used the Classroom Action Research (CAR) method. The data obtained in this study were based on the results of observations and interviews. Observations were made to children while interviews were conducted with parents, class teachers and also recipients of alms in this case the caretaker of the nearest mosque around the school. The results of this study state that children can carry out the habit of giving alms not only at school, but also in the environment around the house, in addition, children also understand the meaning of alms and the reward of alms apart from the teacher's explanation, also through examples that parents do. In addition, parents at RA KPM Al-Ikhlas are also very big in supporting every implementation of children's learning activities. This habit of giving alms is expected to continue to be carried out by children wherever they are. Through this habit, children also become more familiar with the rewards that Allah promises to His servants who give alms. Based on the results of the interview, the obstacles found in the implementation of this habit were not too obstructive, because these obstacles only occurred in 2 parents, where parents did not get enough information from the teacher because they rarely had a quota. In addition, parents also met with teachers so they rarely missed reading information